2015
DOI: 10.1007/s11274-015-1829-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of inorganic and organic nitrogen on the growth and microcystin production of Microcystis aeruginosa

Abstract: Nitrogen causes the frequent occurrence of harmful algal blooms and possible microcystin production. The effects of ammonia and alanine (Ala) on the growth and microcystin production of Microcystis aeruginosa were investigated using an isotope tracer ((15)N). The results indicated that Ala was directly used by M. aeruginosa and contributed to biomass formation amounting to 2.1 × 10(7) cells mL(-1) on day 48, compared with only 6.2 × 10(6) cells mL(-1) from ammonia alone. Microcystin-LR production with Ala was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Intracellular MC production is influenced directly by MC-containing cyanobacteria and indirectly by environmental factors [ 25 ]. Various studies [ 12 , 48 , 49 , 50 ] have investigated the role of environmental factors, including temperature, pH, light [ 51 ], nitrogen [ 24 ] and phosphorus [ 8 ] in the regulation of MC production. However, due to geographic distance, differing lake conditions and variation in analytical methods, no consistent conclusions have been reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular MC production is influenced directly by MC-containing cyanobacteria and indirectly by environmental factors [ 25 ]. Various studies [ 12 , 48 , 49 , 50 ] have investigated the role of environmental factors, including temperature, pH, light [ 51 ], nitrogen [ 24 ] and phosphorus [ 8 ] in the regulation of MC production. However, due to geographic distance, differing lake conditions and variation in analytical methods, no consistent conclusions have been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that cyanobacteria biovolume, Chl-a and DOC had a positive effect, and nitrate, nitrite and DIC had a negative effect on MC-YR production. While some studies have focused on MC-LR and MC-RR [ 48 , 49 , 50 , 61 , 65 ], there has been much less focus on MC-YR. Given that MC-YR is almost as toxic as MC-LR according to toxicity equivalent factors (TEF) [ 66 , 67 ], more attention is warranted to better understand how environmental factors influence its production.…”
Section: Discussionmentioning
confidence: 99%
“…And the biosynthesis of MC may be inuenced by the different forms of nitrogen. 22,23 In addition, previous results indicated positive relationships between nitrogen supply, MC production and MC content in M. aeruginosa. 33 And ammonia could facilitate the synthesis of MC in toxic strains of M. aeruginosa, which were more responsive to ammonia than non-toxic strains.…”
Section: Discussionmentioning
confidence: 86%
“…Through LC-MS-MS analysis, Yan et al 22 cultured a strain of M. aeruginosa and found that ammonia was incorporated into the Arg residue in MC-LR. However, the MC biosynthesis in M. aeruginosa PCC7806 analyzed by genetic tools indicated that Adda was the rst unit to be synthesized, followed by Glu, Mdha, Ala, Leu, MeAsp and Arg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation